The role of key genes in astaxanthin biosynthesis in Phaffia rhodozyma by transcript level and gene knockout. (February 2022) - Li, Zhipeng; Chen, Lina; Yang, Haoyi; Li, Tianli; Du, Xiping; He, Ning; Jiang, Zedong; Li, Lijun; Ni, Hui
Graphical abstract: Highlights: CRTS (4-ketolase/3-hydroxylase) was in dicyclic pathway of astaxanthin biosynthesis. CRTYB (lycopene beta-cyclase) played a role in dicyclic and monocyclic pathway. CRTS and CRTYB were possible rate-limiting enzymes of carotenoids biosynthesis. Abstract: Phaffia rhodozyma is a potential industrial source of natural astaxanthin. Dicyclic and monocyclic pathways of carotenoid synthesis are important nodes in Phaffia rhodozyma, but the relationship between the two pathways and astaxanthin production remains unclear. Eight genes related to dicyclic and monocyclic pathways in three different strains of P. rhodozyma were analysed, and the relationship between expression and astaxanthin biosynthesis was explored. Among these genes, CRTS genes (R = 0.69, P < 0.05) and CRTYB (R = 0.75, P < 0.05) showed the closest correlations with carotenoid and astaxanthin biosynthesis, respectively. To further study these relationships in detail, the CRTYB and CRTS genes were knocked out by homologous recombination. After CRTYB knockout, astaxanthin was decreased to an undetectable level. This result suggested that CRTYB plays a role in dicyclic and monocyclic pathways. Meanwhile, the CRTS gene was in the dicyclic pathway of astaxanthin biosynthesis, and its knockout promoted the monocyclic pathway and resulted in a 25 % increase in astaxanthin production at 120 h. The possible rate-limiting enzymes were the enzymes encoding CRTS and CRTYB by regression analysis. Knockout of the CRTS and CRTYB genes was helpful in understanding the synthetic pathway of astaxanthin and significant to the industrial application of astaxanthin production.